Dampak dari Kehadiran Bisnis Internasional bagi Indonesia - Cahya Adetrya; Hendra Ibrahim (FEB Universitas Maritim Semarang, 2024)
International business is a business activity carried out between countries by carrying out export and import activities. International trade is the exchange of goods and services across international borders. This usually comes with additional risks caused by changes in exchange rates. The purpose of this analysis is to find out about the influence of international business on Indonesia. In this type of research the author uses descriptive research and collects information and analyzes data using secondary data. From this analysis, it can be seen the influence and impact of international business on Indonesia.